P05.28 Karnofsky performance score of brain tumor patients depends on clinician status. (19th September 2018) - Frappaz, D; Taillandier, L; Levard-Bonneville, A; Sore, J; Ricard, D; Schiffler, C; Weller, M
Abstract: RATIONALE: Inclusion criteria for oncological protocols often use the Karnofsky performance score (KPS)>=70 or the WHO performance score (WHO PS) 0–2 as a cut-off value. Inclusion of neuro-oncology patients may be hampered, when general condition is preserved, but performance is decreased due to physical handicap. The assessment of KPS is subjective in such situation. The goal of the current study is to compare the KPS assessment according to the status of the clinician. Methods: A cross-sectional survey was conducted through ANOCEF and EANO networks. Six different clinical situations concerning patients with brain tumor (from youngest and most fit to oldest and crippled with comorbidities) were described in a questionnaire. Clinicians assessed KPS for each situation. Results: 276 clinicians provided an answer, but only 180 completed the 6 cases and are the subject of this analysis. Clinicians homogeneously attributed decreasing KPS from case 1 to 6. There was no difference of assessment between sexes of the clinicians. When clinicians were grouped by age (<40 vs 41–50 vs > 50 year old), the older group rated significantly worse (p 0.0012) and would include less patients (p0.047) if KPS 70 was considered as a cut off. When clinicians were grouped by speciality (residents/general practionner vs neurosurgeons/neurologists vs oncologists), the former rated worse/included less and the latter rated higher/included more patients in trials (p<0.0001 and <0.0001 respectively). Clinicians that were not used to include patients in trials rated worse (especially for most severe cases) and included less patients in trials (p respectively <0.0001 and <0.0008). French and non-French clinicians rated and included patients in a similar way. In a multivariate analysis, age and speciality (both <0.0001) correlate with KPS rating and with possible inclusion in trial (p 0.007 and <0.0001 respectvely). Conclusion: Karnofsky performance score applied to patients with brain tumor is clinician dependant: younger clinicians, oncologists, and clinicians used to include patients in trial will significantly propose a KPS more elevated, especially >=70 that allow inclusion in a trial. Specific rules should be proposed to homogenise inclusion criteria for patients with neurological deficits. Acknowledgment to clinicians that answered to the questionnaire.